Multifunctional coatings of polymeric films for biofilm-mediated infections - Soares, Íris de Brito (2021)
Implant related infections, mainly caused by Staphylococcus aureus, are a public health concern. Treatment is challenging due to multi-resistant strains, and S. aureus ability to adhere and form biofilm on bone and implant surfaces, as well as to invade and persist in osteoblast cells. The present work consisted in the preparation and evaluation of novel dual polymeric film coatings in stainless steel that provide local and controlled antibiotic delivery for the treatment of implant-related infections. Multilayers of chitosan, polymethylmethacrylate (PMMA) and polycaprolactone (PCL) loaded with microspheres containing vancomycin or daptomycin were produced using the dip-coating technique. To enhance polymeric film adhesion on the surface of the metallic substrate, different surface treatments were evaluated such as chemical etching, electrochemical etching, and mechanical abrasion. From this study, it was possible to conclude that the mechanical abrasion showed the best results. After films production optimization, morphological, chemical, and mechanical properties were evaluated in detail for the several film combinations. Finally, the drug-release studies of daptomycin and vancomycin were carried out for drug and microsphere loaded films. It was possible to conclude that the release is mainly diffusion dependent. In summary, this work has shown that the films obtained exhibit promising characteristics to be used in the context of implant-related infection treatment.